Ein erhöhtes Risiko von Wirbelsäulenverletzung bei Hochleistungsturnern während des puberalen Wachstums - Lohrer, H. (Wiener Medizinische Wochenschrift, 1998)
Elite womens gymnastics has generally been described to induce vertebral overload injuries, especially in the pubertal growth phase. This paper describes the results of a 4-year prospective longitudinal and transversal investigation of German elite womens gymnasts with respect to the spine. The main results are: 1) Pathological changes are detectable by clinical investigation before X-ray abnormalities can be found. 2) A sensitive test is the spine springing test. 3) Functional abnormalities can be detected especially in the lumbosacral region. 4) There were no spondylolyses. 5) Osteochondrotic lesions are frequent. They are concentrated in the dorsolumbar region.